Formation and reformulation : the redaction of the book of Joshua in the light of the oldest textual witnesses - Meer, Michaël N. van der. (Vetus Testamentum, Supplements, 2004)
This volume offers a critical examination of recent theories concerning the growth of biblical literature in the light of the oldest textual witnesses (the Qumran biblical scrolls and the Septuagint). On the basis of a fresh examination of a selection of passages in the book of Joshua, it is shown that these witnesses do not reflect a stage in the literary formation of the book prior to the standardised (Masoretic) text, but a reinterpretation and reformulation of its contents. The study presents a new literary-critical solution to the intricate problems of Joshua 8 and a detailed exegesis of the Greek version of Joshua 1 and 5. Of special interest for Qumran scholars is the new reconstruction of 4QJoshuaª.